Functional Movement Screen: Pain versus composite score and injury risk. (November 2017) - Alemany, Joseph A.; Bushman, Timothy T.; Grier, Tyson; Anderson, Morgan K.; Canham-Chervak, Michelle; North, William J.; Jones, Bruce H.
Abstract: Objectives: The Functional Movement Screen (FMS™) has been used as a screening tool to determine musculoskeletal injury risk using composite scores based on movement quality and/or pain. However, no direct comparisons between movement quality and pain have been quantified. Design: Retrospective injury data analysis. Methods: Male Soldiers (n = 2154, 25.0 ± 1.3 years; 26.2 ± .7 kg/m 2 ) completed the FMS (scored from 0 points (pain) to 3 points (no pain and perfect movement quality)) with injury data over the following six months. The FMS is seven movements. Injury data were collected six months after FMS completion. Sensitivity, specificity, receiver operator characteristics and positive and negative predictive values were calculated for pain occurrence and low (≤14 points) composite score. Risk, risk ratios (RR) and 95% confidence intervals were calculated for injury risk. Results: Pain was associated with slightly higher injury risk (RR = 1.62) than a composite score of ≤14 points (RR = 1.58). When comparing injury risk between those who scored a 1, 2 or 3 on each individual movement, no differences were found (except deep squat). However, Soldiers who experienced pain on any movement had a greater injury risk than those who scored 3 points for that movement (p < 0.05). A progressive increase in the relative risk occurred as the number of movements in which pain occurrence increased, so did injury risk (p < 0.01). Conclusions: Pain occurrence may be a stronger indicator of injury risk than a low composite score and provides a simpler method of evaluating injury risk compared to the full FMS.